Ice bear - Davies, Nicola 1958- (Walker Books, 2005)
Describes in a picture book format, how the polar bear, also called Nanuk, thrives in the Arctic and explains the lessons that the Inuit people have learned from watching the creature. Suggested level: junior, primary
Includes index
Keywords: Polar bear / Juvenile fiction; Polar bear / Fiction; Inuit / Fiction; Bears / Fiction; Ours blanc / Romans, nouvelles, etc. pour la jeunesse; Polar bear; Children's nonfiction; Fiction; Juvenile works; Bilderbuch; Sachbilderbuch